Increased serum cotinine and obesity negatively impact asthma exacerbations and hospitalizations: A cross-sectional analysis of NHANES. Issue 1 (6th December 2023) - Greiner, Benjamin; Elenwo, Covenant; Hartwell, Micah
Abstract: Background: Asthma is the most common non-communicable chronic airway disease worldwide. Obesity and cigarette use independently increase asthma morbidity and mortality. Current literature suggests that obesity and smoking synergistically increase asthma-related wheezing. Objective: To assess whether increased serum cotinine and obesity act synergistically to increase the likelihood of having an asthma exacerbation, emergency department (ED) visit, or hospitalization. Methods: A cross-sectional analysis of the 2011–2015 iterations of NHANES database was performed. Patients aged 18 years or greater with asthma were included. Serum cotinine was utilized as an accurate measurement of cigarette use. Logistic regression models were constructed to determine whether elevated serum cotinine and obesity were associated with self-reported asthma exacerbations, asthma-specific ED usage, and hospitalizations for any reason in the past year. Odds ratios were adjusted for age, gender, race, and ethnicity. Interactions were assessed by multiplying the adjusted effect sizes for elevated cotinine and obesity. Results: We identified 2179 ( N = 32, 839, 290) patients with asthma, of which 32.2% were active smokers and 42.7% were obese. Patients with an elevated cotinine and asthma were significantly more likely to have had an asthma-related ED visit in the past year (adjusted odds ratio [AOR] 1.82; 95% CI 1.19–2.79), have a physician-prescribed asthma medication (AOR 2.04; 95% CI 1.11–3.74), and have a hospitalization for any reason (AOR 3.65; 95% CI 1.88–7.07) compared to those with low cotinine. Patients with asthma and obesity were more likely to have an asthma-related ED visit (AOR 1.67; 95% CI 1.06–2.62) or hospitalization for any reason in the past year compared to non-obese patients (AOR 2.76; 95% CI 1.69–4.5). However, a statistically significant interaction between obesity and cotinine was only identified in patients who currently have asthma compared to a previous asthma diagnosis (AOR 1.76; 95% CI 1.10–2.82). There were no synergistic interactions among ED usage or asthma exacerbations. Conclusion: Nearly one-third of patients with asthma were current smokers, and almost half were obese. This study identified elevated serum cotinine, a metabolite of cigarette use, and obesity as key risk factors for asthma exacerbations, asthma-related ED visits, and hospitalizations for any reason. Elevated serum cotinine and obesity were not found to act synergistically in increasing asthma exacerbations or ED visits. However, the presence of both risk factors increased the risk of currently having asthma (compared to a previous diagnosis) by 76%. Serum cotinine may be useful in predicting asthma outcomes.